2009
DOI: 10.1098/rsbl.2009.0575
|View full text |Cite
|
Sign up to set email alerts
|

Rapid adaptive evolution of northeastern coyotes via hybridization with wolves

Abstract: The dramatic expansion of the geographical range of coyotes over the last 90 years is partly explained by changes to the landscape and local extinctions of wolves, but hybridization may also have facilitated their movement. We present mtDNA sequence data from 686 eastern coyotes and measurements of 196 skulls related to their two-front colonization pattern. We find evidence for hybridization with Great Lakes wolves only along the northern front, which is correlated with larger skull size, increased sexual dimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
226
4
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(243 citation statements)
references
References 18 publications
12
226
4
1
Order By: Relevance
“…Tables 3 and 4, respectively. (Kays et al, 2010;Way et al, 2010) suggests that the size hypothesis may be less applicable in the case of eastern wolf-coyote hybridization, but does not preclude the general trend observed in our data set where coyote mtDNA was present in NEON grey wolves but coyote and ancestral Y chromosome DNA was absent, and grey wolf mtDNA was present in FRAX coyotes but grey wolf Y chromosome DNA was absent. The Bayesian and multivariate analyses used in this study revealed a complex history of repeated hybridization events in Ontario Canis populations.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Tables 3 and 4, respectively. (Kays et al, 2010;Way et al, 2010) suggests that the size hypothesis may be less applicable in the case of eastern wolf-coyote hybridization, but does not preclude the general trend observed in our data set where coyote mtDNA was present in NEON grey wolves but coyote and ancestral Y chromosome DNA was absent, and grey wolf mtDNA was present in FRAX coyotes but grey wolf Y chromosome DNA was absent. The Bayesian and multivariate analyses used in this study revealed a complex history of repeated hybridization events in Ontario Canis populations.…”
Section: Discussionmentioning
confidence: 42%
“…Haplotypes C1 and C3 are considered eastern wolf specific based on previously published phylogenetic analyses (Wilson et al, 2000;Rutledge et al, 2009). Although haplotypes C9, C13 and C17 cluster phylogenetically with coyote haplotypes, leading some to interpret them as coyote specific (for example, Leonard and Wayne, 2008;Kays et al, 2010), they are interpreted here as eastern wolf specific because they are not known to occur in non-hybridized western coyote populations; their presence in eastern wolves is due to either incomplete lineage sorting or hybridization during the last glaciation event B11 000 years ago (Wheeldon and White, 2009). This assumption is reasonable, given the presence of coyote-like haplotypes in eastern wolves approximately 30-400 years before western coyote expansion Rutledge et al, 2009), and the assignment of a coyote-like sequence as red wolf (C. rufus) specific (Hailer and Leonard, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…To test for signals of population expansion, we calculated a mismatch distribution and conducted two neutrality tests (Tajima's D, Fu's Fs). We excluded samples from the most recently (last century) colonized eastern North America because recurrent gene flow between the invading coyotes and resident eastern wolves [9][10][11] might bias demographic inferences. Past population size trajectories were inferred using a Bayesian coalescent (Bayesian Skyline Plot, BSP [3]) approach as implemented in BEAST v. 1.5.4 [12].…”
Section: Methodsmentioning
confidence: 99%
“…However, this human disturbance alone has not been responsible for all expansions; hybridization has contributed significantly as well [3]. As coyotes moved into areas occupied by grey wolf populations (Canis lupus) both species interbreed and this may allow for a much quicker colonization rate, facilitating their expansion [3] [11] [12]. Canis lantrans mtDNA was found in wolf populations [13] [14] [15] and other studies have shown the opposite [3].…”
mentioning
confidence: 99%
“…These areas have the potential to host more prey items [2] [10] [11]. However, this human disturbance alone has not been responsible for all expansions; hybridization has contributed significantly as well [3]. As coyotes moved into areas occupied by grey wolf populations (Canis lupus) both species interbreed and this may allow for a much quicker colonization rate, facilitating their expansion [3] [11] [12].…”
mentioning
confidence: 99%